An Exploration of the Causes of Cost Overruns in Public Sector Infrastructure Projects in the United Arab Emirates (UAE): A Stakeholder Perspective - FANOUSSE, RIM IMAD (2017)
In this research paper, the light is shaded on cost overrun as one of the hot topics that is becoming commonly a phenomenal issue in the projects worldwide. In spite of the considerable developed knowledge in project management, cost overrun is inherently forming a part for the most of the infrastructure projects. Today, the degree of project’s success is measured by being within the golden triangle of cost, scope and time. Therefore, this proposed dissertation is investigating the factors that cause costs to overrun in public sector infrastructure projects specifically in UAE from perspective of clients and contractors as well as consultants who are the main three stakeholders. An extensive literature review was demonstrated at the aim of studying the major factors causing costs to overrun in public sector infrastructure projects in UAE. Several causes of cost overrun were accordingly explored. Quantitative research techniques were subsequently conducted as to collect data from the three key stakeholders according to their expertise in any of the public sector infrastructure projects in the UAE that come across the issue of cost overrun. The quantitative research approach investigation was done through the use of online questionnaire technique as to examine the relationship amongst the overrun issue pertains to project’s costs and causes triggered cost overrun of public sector infrastructure projects in UAE. The analysis confirmed that the studied causes of cost overrun with its independent variables of (inadequate project management, funding problem, improper cost estimation, payment delay, poor tendering documents, inappropriate contractors selection, lack of contractors experience, contractors financing, frequent design changes during the construction, and poor material management) do correlate with cost overrun variable and 80.0% of the change in the project cost overrun issue can be explicated via the variability of these studied causes of cost overrun. According to the analysed data, a number of significant recommendations were suggested to be undertaken at the aim of minimising the issue of costs overrun accompanying with the public sector infrastructure projects. The suggested recommendations include the adoption of effective strategic planning along with the efficient management of communication undertaken amongst the entire project’s stakeholders. Besides, engaging experienced and highly qualified contracts in addition to having proper advanced project planning and scheduling tools and charts would ensure a successful attainment of project’s objectives. A constant control and measure of the overall project’s progress was also recommended along with the integration of value management as to accomplish the best cost design options. A well documentation of project’s designs prior to sharing them would enhance the performance of the employed contractors pertaining to the required material management too. All in all, the suggested recommendations if implemented would eliminate project cost overrun and enable projects to move towards successful completions.